2011
DOI: 10.1002/jccs.201190141
|View full text |Cite
|
Sign up to set email alerts
|

Sterols from the Stems of Momordica charantia

Abstract: A new sterol, 5a,6a-epoxy-3b-hydroxy-(22E,24R)-ergosta-8,22-dien-7-one (1), together with eight known sterols, 5a,6a-epoxy-(22E,24R)-ergosta-8,22-diene-3b,7a-diol (2), 5a,6a-epoxy-(22E,24R)-ergosta-8,22-diene-3b,7b-diol (3), 5a,6a-epoxy-(22E,24R)-ergosta-8(14),22-diene-3b,7a-diol (4), 3b-hydroxy-(22E,24R)-ergosta-5,8,22-trien-7-one (5), ergosterol peroxide (6), clerosterol (7), decortinol (8), and decortinone (9), were isolated from the stems of Momordica charantia. Their structures were elucidated by mean of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…The very small J value of H-6 and H-7 ( J = 2.5 Hz) confirmed that these protons did not have the same axial orientation. The 13 C NMR data of C-5 (δ C 65.6), C-6 (δ C 62.6), and C-9 (δ C 134.5) of 1 were very similar to the corresponding data of 5 α ,6 α -epoxy-(22 E ,24 R )-ergosta-8,22-diene-3 β ,7 α -diol ( 1a ) (δ C 65.7, 62.6, and 134.4, respectively), 17 5 α ,6 α -epoxy-23-demethylgorgost-8-ene-3 β ,7 α -diol (δ C 65.6, 62.6, and 134.6, respectively), 21 and (24 R )-5 α ,6 α -epoxy-24-ethylcholest-8-ene-3 β ,7 α -diol (δ C 65.6, 62.5, and 134.5, respectively) 22 measured in the same solvent (CDCl 3 ). In addition, the chemical shifts of H-18 ( δ H 0.59) and H-19 ( δ H 1.14) of 1 were similar to the experimental, as well as the computational data for the structure 3 β ,7 α -dihydroxy-5 α ,6 α -epoxy-Δ 8 .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The very small J value of H-6 and H-7 ( J = 2.5 Hz) confirmed that these protons did not have the same axial orientation. The 13 C NMR data of C-5 (δ C 65.6), C-6 (δ C 62.6), and C-9 (δ C 134.5) of 1 were very similar to the corresponding data of 5 α ,6 α -epoxy-(22 E ,24 R )-ergosta-8,22-diene-3 β ,7 α -diol ( 1a ) (δ C 65.7, 62.6, and 134.4, respectively), 17 5 α ,6 α -epoxy-23-demethylgorgost-8-ene-3 β ,7 α -diol (δ C 65.6, 62.6, and 134.6, respectively), 21 and (24 R )-5 α ,6 α -epoxy-24-ethylcholest-8-ene-3 β ,7 α -diol (δ C 65.6, 62.5, and 134.5, respectively) 22 measured in the same solvent (CDCl 3 ). In addition, the chemical shifts of H-18 ( δ H 0.59) and H-19 ( δ H 1.14) of 1 were similar to the experimental, as well as the computational data for the structure 3 β ,7 α -dihydroxy-5 α ,6 α -epoxy-Δ 8 .…”
Section: Resultssupporting
confidence: 79%
“…Detailed analysis of the 1 H and 13 C NMR data indicated that the structure of 1 was similar to those of 5α,6α-epoxy-(22E)-ergosta-8,22-diene-3β,7α-diol, except for the addition of a terminal double bond at C-25/C-26 (Table 1). [17][18][19][20] These suggestions were further confirmed by the HSQC, COSY, and HMBC spectra. The HMBC correlations from (δ C 62.6), and C-9 (δ C 134.5) of 1 were very similar to the corresponding data of 5α,6α-epoxy-(22E,24R)-ergosta-8,22diene-3β,7α-diol (1a) (δ C 65.7, 62.6, and 134.4, respectively), 17 5α,6α-epoxy-23-demethylgorgost-8-ene-3β,7α-diol (δ C 65.6, 62.6, and 134.6, respectively), 21 and (24R)-5α,6α-epoxy-24-ethylcholest-8-ene-3β,7α-diol (δ C 65.6, 62.5, and 134.5, respectively) 22 measured in the same solvent (CDCl 3 ).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The structures of these compounds were established based on their NMR, HRESIMS, IR, ECD, and single‐crystal X‐ray diffraction data. Two known compounds were confirmed to be (3 β ,5 α ,6 α ,22 E )‐5,6‐epoxy‐3‐hydroxyergosta‐8,22‐dien‐7‐one ( 3 ), [ 32 ] and calvasterol B ( 4 ) [ 33 ] by comparing their NMR spectroscopic data as well as specific rotations with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%